A new species and a new record of the genus Squamulea (Teloschistaceae, lichenized Ascomycota) from Pakistan. (20th March 2023) - Afshan, Najam-ul-Sehar; Fayyaz, Iram; Iftikhar, Fatima; Jabeen, Maria; Khalid, Abdul Nasir
Abstract: A novel species in the genus Squamulea, S. chikarensis, is described from Himalayan moist temperate forest in Pakistan. The morphology, chemistry and ITS sequences support its distinction from other species of this genus. The taxon is characterized by a pale green to yellow thallus, large apothecia up to 0.8–1.8 mm wide, pale yellow to yellow-orange apothecial discs, a hymenium 70–110 μm high, large ascospores (12–20 × 5–11 μm) and a narrow ascospore septum (1.5–3 μm). In addition, S. flakusii is reported as new to Pakistan and Eurasia.